1987
DOI: 10.1042/bj2470175
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory action of polyamines on protein kinase C association to membranes

Abstract: Physiological activation of protein kinase C requires the interaction of this enzyme with cellular membranes [Nishizuka (1986) Science 233,[305][306][307][308][309][310][311][312]. In the present work a reconstituted system of protein kinase C and human inside-out erythrocyte vesicles was utilized to study the effect in vitro of naturally occurring polyamines on the activation process of protein kinase C. The active membrane-associated complex was conveniently determined by its ability to bind radioactive pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

1988
1988
2009
2009

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 44 publications
1
22
0
2
Order By: Relevance
“…Furthermore, Ca2+ appears to be more specific than Mg2+. A similar competition between polyamines and calcium for binding to PM was earlier observed by Moruzzi et al (1987) in human erythrocyte membrane vesicles, where it was proposed to represent a mechanism to modulate protein kinase C activation. On the other hand, the inhibition of spermidine binding by calcium may also reflect an activation of proteases.…”
Section: Dlscusslonsupporting
confidence: 71%
“…Furthermore, Ca2+ appears to be more specific than Mg2+. A similar competition between polyamines and calcium for binding to PM was earlier observed by Moruzzi et al (1987) in human erythrocyte membrane vesicles, where it was proposed to represent a mechanism to modulate protein kinase C activation. On the other hand, the inhibition of spermidine binding by calcium may also reflect an activation of proteases.…”
Section: Dlscusslonsupporting
confidence: 71%
“…Phorbol esters, which activate protein kinase C, inhibit the L-type channel current in this preparation (Linden & Routtenberg, 1989). Putrescine is known to inhibit protein kinase C but does not affect the cyclic AMP-dependent protein kinase (Qi, Schatzman, Mazzei, Turner, Raynor, Liao & Kuo, 1983;Thams, Capito & Hedeskov, 1986;Moruzzi, Barbiroli, Monti, Tadolini, Hakim & Mezzetti, 1987). It was therefore hypothesized that the effect of putrescine might be mediated via protein kinase C.…”
Section: Discussionmentioning
confidence: 99%
“…This was borne out in model systems. Moruzzi et al (1987), using protein kinase C purified from rat brain and inside-out human erythrocyte membrane vesicles, were able to show that micromolar concentrations of spermine (spermidine was much less potent) greatly interfered with the formation of the active membraneassociated enzyme complex. That this might not be the only explanation for the inhibitory action of polyamines on protein kinase C activity was verified by the same group, which showed that spermine at millimolar concentrations interacted also with the catalytic domain of the enzyme and strongly inhibits its phosphorylation activity (Mezzetti et al, 1988).…”
Section: Polyamines and Transportmentioning
confidence: 99%